Визначення компонентів психофізичної готовності поліцейських до застосування табельної вогнепальної зброї в умовах воєнного стану - Боровик, М. О.; Borovyk, M. O.; Надутий, А. В.; Nadutyi, A. V.; Лукін, Б. П.; Lukin, B. P.; Надутий Андрій Валерійович; Боровик Микола Олександрович (Право і безпека. – 2023. – № 1 (88). – С. 44-55, 2023)
Проведено аналіз джерел міжнародного та вітчизняного права, що регламентують застосування поліцейськими сили, спеціальних засобів і вогнепальної зброї. Виокремлено особливості правового регулювання застосування примусових поліцейських заходів в Україні в умовах воєнного стану. Наведено чинники, які впливають на прийняття поліцейськими рішення про можливість застосування табельної вогнепальної зброї. Здійснено порівняльну характеристику показників власників вогнепальної зброї на 100 тис. населення закордоном з аналогічним показником в Україні. Запропоновано шляхи комплексного поєднання зазначених напрямів психофізичної готовності до застосування табельної вогнепальної зброї.

The scientific work is aimed at finding ways to improve the components of the psychophysical readiness of police officers to use service firearms. In order to solve the research tasks, an analysis of the sources of international and domestic law regulating the use of force, specialmeans, and firearms by the police has been carried out, including the UN Code of Conduct for Law Enforcement Officials, the Declaration on the Police, Basic Principles of the Use of Force and Firearms by Officials on maintaining law and order, the Constitution of Ukraine,the Criminal Code of Ukraine,the Law of Ukraine “On the National Police”, Regulations on the organization of official training of employees of the National Police of Ukraine, Instructions on safety measures when handling weapons, Regulations on the organization of initial professional training of police officers who are first accepted on police service.The algorithm for applying coercive police measures proposed by the UN hs beenconsidered, that is communication – persuasion – physical force – special means – firearms. A comparativecharacterization of the indicators of firearm owners per 100,000 population abroad with asimilar indicator in Ukraine has been carried out. The peculiarities of the legal regulation of the use of coercive police measures in Ukraine under martial law conditions have been determined. The legal, social, domestic and psychophysiological factors that affect the decision-making by police officers on the possibility of using a registered firearm have been given. Based on the conducted research, the study of special literature, and the analysis of the activities of practical police officers who have at least 5 years of service, it has been established that the components of psychophysical readiness for the use of service firearms are physical, psychological, fire (shooting) and tactical-special training. Ways of a complex combination of the specified areas of psychophysical readiness for the use of service firearms have been proposed.

Проведен анализ источников международного и отечественного права, регламентирующих применение полицейской силы, специальных средств и огнестрельного оружия. Выделены особенности правового регулирования применения принудительных полицейских мер в Украине в условиях военного положения. Указаны факторы, которые влияют на принятие полицейскими решения о возможности применения табельного огнестрельного оружия. Проведена сравнительная характеристика показателей владельцев огнестрельного оружия на 100 тыс. населения за границей с аналогичным показателем в Украине. Предложены пути комплексного сочетания указанных направлений психофизической готовности к применению табельного огнестрельного оружия.
Determining the components of the psychophysical readiness of police officers to use service firearms under martial law conditions
Определение компонентов психофизической готовности полицейских к применению табельного огнестрельного оружия в условиях военного положения
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; поліцейські; police officers; полицейские; психофізична готовність; psychophysical readiness; психофизическая готовность; табельна вогнепальна зброя; registered firearm; табельное огнестрельное оружие; воєнний стан; martial law; военное положение; правове регулювання; legal regulation; правовое регулирование